The role of community in the development of elite handball and football players in Denmark - Rossing, N. N.; Nielsen, A. B.; Elbe, A.-M.; Karbing, D. S. (European Journal of Sport Science, 2016)
The primary purpose of this study was to investigate the effect of the place of early development in a sample of Danish male elite and youth handball and football players. The sample included 366 handball and football players from the elite Danish league in the season 2011-2012 and a comparison sample of youth players under the age of 12 from 2003, including 147,221 football and 26,290 handball players. Odds ratio analysis showed that both population size and density significantly affected the proportional number of youth players per community and the odds of athletes reaching an elite level in football and handball. The odds for youth player registrations in both handball and football increased in rural in contrast to urban communities. However, elite football players primarily came from communities of high density (>1000 pop./km2), whereas elite handball players primarily came from less densely populated communities (100 to <250 pop./km2). Furthermore, there seems to be a relation between representation of elite and talent clubs in different communities and the probability of becoming an elite player in both sports. The limited number of elite players in both sports from rural communities may be due to national talent development strategies that do not incorporate development support for clubs in rural areas. Additionally, the results of the study clearly suggest the need to include the youth player population to advance research findings in birthplace effect studies.